2012
DOI: 10.1007/s13762-012-0054-6
|View full text |Cite
|
Sign up to set email alerts
|

Biosorptive behaviour of mango leaf powder and rice husk for arsenic(III) from aqueous solutions

Abstract: The present study deals with the biosorption of As(III) from aqueous solution using mango leaves powder (MLP) and rice husk (RH) in a batch operation. Scanning electron microscopy and Fourier transformation infrared spectrometry analysis shows the surface texture of biosorbents and metal binding of functional groups of before and after biosorption of As(III). The optimum pH was obtained at 7 and 6 with 7 and 6 g/l of dosage of MLP and RH, respectively. The adsorption of As(III) onto MLP and RH was favourably i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 62 publications
3
24
0
Order By: Relevance
“…Therefore, an inexpensive alternative to activated carbon can greatly increase the application of adsorption based method in various developing countries like Bangladesh. Materials such as tea waste, microbial biomass and straw etc., have already been tested generally as low-cost adsorbent (Aikpokpodion et al 2010;Amarasinghe and Williams 2007;Bhaina and D'Souza 2001;Cay et al 2004;Ingole and Bhole 2003;Kamsonlian et al 2011;Mahavi et al 2005;Wasewar 2010;Wasewar et al 2008). The use of waste materials as inexpensive adsorbent can have several additional advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an inexpensive alternative to activated carbon can greatly increase the application of adsorption based method in various developing countries like Bangladesh. Materials such as tea waste, microbial biomass and straw etc., have already been tested generally as low-cost adsorbent (Aikpokpodion et al 2010;Amarasinghe and Williams 2007;Bhaina and D'Souza 2001;Cay et al 2004;Ingole and Bhole 2003;Kamsonlian et al 2011;Mahavi et al 2005;Wasewar 2010;Wasewar et al 2008). The use of waste materials as inexpensive adsorbent can have several additional advantages.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of copper and chromium was investigated by the residue of brewed tea from aqueous solutions, and it was shown that adsorbent dose, and copper and chromium ion concentrations, in such solutions influenced the degree of obviation of these heavy metal ions (Dizadji and Abootalebi 2011). Recently, Kamsonlian et al evaluated the effectiveness of some biomass prepared from mango leaf powder and rice husk to remove As(III) from aqueous solutions (Kamsonlian et al 2012). The batch removal of hexavelant chromium from aqueous solutions using almond shell, activated sawdust and activated carbon under different experimental conditions was investigated (Aliabadi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the aquatic environment, it exists in different forms such as arsenious (H 3 AsO 3 , H 3 AsO 3 , H 3 AsO 3 2-), arsenic (H 3 AsO 4 , H 3 AsO 4-, H 3 AsO 4 2-), arsenites [As(III)], arsenates [As(V)], methylarsenic, dimethylarsinic acid, and arsine . Its long-term exposure causes a variety of serious health issues such as dermal changes (pigmentation, hyperkeratoses, and ulceration), respiratory, neurological, cardiovascular, vomiting as well as results in the appearance of diverse type of cancer of skin, lung, bladder, and kidney (Guo et al 2007;Mandal and Suzuki 2002;Kamsonlian et al 2012). The toxicity of As exists greatly in its oxidation states (-3, 0, ?3, and ?5), and the trivalent form [As(III)] is recognized as most hazardous state (Manju et al 1998).…”
Section: Introductionmentioning
confidence: 99%